Usulan kebijakan persediaan material untuk meminimasi overstock menggunakan newsvendor model pada PT. XYZ - Meilani, Mela; Ardiansyah , Muhammad Nashir; Muttaqin , Prafajar Suksessanno (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT XYZ is a company engaged in the concrete manufacturing industry. Concrete production at PT XYZ affects the inventory of constituent materials needed in making concrete. The problem of PT XYZ, there is an overstock of basic materials, because there is a gap between the amount of basic material inventory and demand. So, it is necessary to propose an inventory policy to minimize overstock. The problem-solving method used in this research is ABC Analysis to determine the classification of each material and the new vendor model to determine the amount of material inventory. Based on calculations using ABC analysis, material classification is obtained based on three categories, category A one type of material, category B two types of material, and category C four types of material. Calculations using the newsvendor model obtained a decrease in total inventory costs by 10.8% and the amount of material inventory by 20.4%.